Signatures of topological ground state degeneracy in Majorana islands - Vayrynen, Jukka; Feiguin, Adrian E.; Lutchyn, Roman (2020)
The authors study conductance and average charge in a Majorana island coupled to many normal metal leads. The topological ground state degeneracy leads to enhanced charge fluctuations and suppression of Coulomb blockade in conductance.